Analysis of learning objective based on dimensions process cognitive Bloom’s - Dila Nur Wahidah; Riche Cynthia Johan (Inovasi Kurikulum, 2025)
One of the competencies that a teacher must have is designing learning. Learning design must describe the learning objectives to be achieved. Seeing the various demands today, learning must prepare students to have higher-order thinking skills and the 4C’s skills (Creativity, Critical thinking, Collaboration, and Communication). Based on this situation, this study aims to analyze how teachers as learning designers can determine learning objectives to facilitate students in future challenges. This study was conducted on grade VII mathematics teachers in Bandung City who were included in the first generation of Sekolah Penggerak by classifying learning objectives based on Bloom’s cognitive process dimensions. This study uses a qualitative approach with the descriptive, evaluative method. The results of this study indicate that the learning objectives designed by mathematics teacher class VII at Bandung show that three mathematics teachers had determined learning objectives with the dimensions process cognitive achieve LOTS. With this study, it is hoped that more teachers will be able to balance the dimensions process of cognitive Bloom’s as the formulation of learning objectives, especially in the dimensions that equip students to compete in the future.   Abstrak Salah satu kompetensi yang harus dimiliki seorang guru adalah merancang pembelajaran. Perancangan pembelajaran harus menggambarkan tujuan pembelajaran yang hendak dicapai. Melihat berbagai tuntutan pada masa kini, tentu pembelajaran harus mempersiapkan peserta didik supaya memiliki keterampilan berpikir tingkat tinggi dan keterampilan 4C (Creativity, Critical thinking, Collaboration, and Communication). Berlandaskan pada keadaan tersebut, maka penelitian ini hendak menganalisis bagaimana guru sebagai perancang pembelajaran mampu menurunkan tujuan pembelajaran agar dapat memfasilitasi peserta didik dalam menghadapi tantangan di masa depan. Penelitian ini dilakukan kepada guru matematika kelas VII di Kota Bandung yang tergabung dalam sekolah penggerak angkatan pertama dengan mengklasifikasi tujuan pembelajaran berdasarkan dimensi proses kognitif Bloom. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif evaluatif. Adapun hasil penelitian ini menunjukkan bahwa tujuan pembelajaran yang dirancang oleh guru matematika mencapai dimensi proses kognitif LOTS. Implikasi penelitian ini diharapkan semakin banyak guru yang mampu mengimbangi terhadap dimensi proses kognitif Bloom sebagai perumusan tujuan pembelajaran, terlebih pada dimensi yang membekali peserta didik agar mampu bersaing di masa depan. Kata Kunci: dimensi proses kognitif; rancangan pembelajaran; taksonomi Bloom